Labour in a Global World Case Studies from the White Goods Industry in Africa, South America, East Asia and Europe - Nichols, T.; Cam, S.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2005)
This book gets behind much generality about globalisation to examine the production of relatively familiar commodities such as refrigerators and ovens in different countries. By considering a range of countries - China, Taiwan and South Korea, South Africa, Brazil and Turkey - it makes a substantive contribution to the understanding of the diffusion of management methods, the role of the state in employee relations, the nature of trade unionism and the impact of social structure on production relations.
Keywords: International business enterprises; Industrial sociology; International economics; International Business; Sociology of Work; International Economics